The Influence of Auditor Characteristics on Audit Quality - Robbani, Usamah; Subyantoro, Edi; Sihwahjoeni; Pratiwi, Rianti (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study aims to analyse the influence of auditor characteristics on audit quality in Public Accounting Firms (KAP) in Malang City. The characteristics examined include workload, independence, integrity, competence, objectivity, experience, and professionalism. An explanatory survey method with a quantitative approach was employed, involving 57 respondents from 18 KAPs. Data were collected through questionnaires measured using a Likert scale and analysed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. The results indicate that independence, integrity, competence, objectivity, experience, and professionalism have a positive and significant effect on audit quality. In contrast, workload does not show a significant influence. These findings underscore the importance of individual and professional attributes of auditors in ensuring high-quality audits. The coefficient of determination (R²) of 96.4% indicates that auditor characteristics account for a substantial portion of the variability in audit quality. This study provides implications for accounting firms to enhance the professional development of their auditors through ongoing training, integrity reinforcement, and the preservation of professional independence. It also recommends future research to include additional variables and expand the geographic scope to obtain a more comprehensive understanding of the determinants of audit quality in Indonesia.